2015
DOI: 10.1017/neu.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between amygdala volume and impulsivity in adults with attention-deficit hyperactivity disorder

Abstract: Smaller amygdala volumes have been observed in patients with ADHD. Our results suggest that greater emotional processing and less control of impulsivity are associated with smaller amygdala volumes in ADHD patients. Furthermore, the right amygdala would play a bigger role in impulsivity and behaviour control than the left amygdala. Further studies involving larger samples of adult patients with ADHD and using multimodal designs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…In healthy subjects, negative (Boes et al, 2009 ; Matsuo et al, 2009 ; Schilling et al, 2012 , 2013 ) or positive (Gardini et al, 2009 ; Schilling et al, 2012 ; Cho et al, 2013 ) correlations were both reported between impulsivity and GMV/cortical thickness in frontal, temporal regions and amygdala. The significant correlations between GMV in the orbitofrontal cortex (OFC)/amygdala and impulsivity were also found in patients with major depressive disorder, alcoholism, attention-deficit/hyperactivity disorder, posttraumatic stress disorder, antisocial personality disorder and bipolar disorder (Antonucci et al, 2006 ; Tajima-Pozo et al, 2015 ). However, the relationship between impulsivity and GMV in IGD adolescents was largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects, negative (Boes et al, 2009 ; Matsuo et al, 2009 ; Schilling et al, 2012 , 2013 ) or positive (Gardini et al, 2009 ; Schilling et al, 2012 ; Cho et al, 2013 ) correlations were both reported between impulsivity and GMV/cortical thickness in frontal, temporal regions and amygdala. The significant correlations between GMV in the orbitofrontal cortex (OFC)/amygdala and impulsivity were also found in patients with major depressive disorder, alcoholism, attention-deficit/hyperactivity disorder, posttraumatic stress disorder, antisocial personality disorder and bipolar disorder (Antonucci et al, 2006 ; Tajima-Pozo et al, 2015 ). However, the relationship between impulsivity and GMV in IGD adolescents was largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the fronto-cerebellar networks have been implicated in impairments of cognitive control (e.g., over-riding impulses) in both ADHD and obesity [40,41]; the ability to consider future consequences/adjust behaviours [41]; and the inhibition of eating behaviour [42]. Likewise, the amygdala and hippocampus have been associated with impulsivity symptoms in ADHD [43] as well as weight gain and overeating behaviours such as continuing to eat even when sated [44][45][46][47]. Finally, the orbital frontal cortex has been linked to impairments in cognitive and attentional control in ADHD [48], but also potentially to selection and consumption of calorie-rich foods [49] and sensitized reactivity to (foodrelated) reward [50].…”
Section: Discussionmentioning
confidence: 99%
“…delay-discounting - Ainslie, 1974). Interestingly, patients with damage to the amygdala or to the orbital frontal cortex show poor decision-making and are often described as impulsive (Gopal et al, 2013;Tajima-Pozo et al, 2015). These same brain regions are also thought to be involved in the mediation and aetiology of psychopathic traits (Stratton et al, 2015).…”
Section: 1factor 1: Interpersonal/affectivementioning
confidence: 99%